A Clinical study of amniotic fluid index at or beyond 28 weeks of gestation and its relation to perinatal outcome - Chetani, Monica; Deepika, .; Khajotia, Santosh; Kochar, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Amniotic fluid plays a major role in the development of fetus. It provides a medium in which fetus can readily move, cushions the fetus against injuries, helps to maintain even temperature. Objective of present study was to investigate the perinatal outcome of ultrasonographically detected normal and decreased (Oligohydramnios) amniotic fluid index, at or beyond 28 weeks of gestation. Methods: During this study 200 patients with singleton pregnancy were selected at or beyond 28 weeks of pregnancy and AFI was evaluated. On the basis of AFI measurement patients were divided in two groups. Perinatal outcome in pregnancies with AFI of <5cm were compared with those with normal AFI. Results: There was significant correlation (p<0.001) between oligohyramnios and poor perinatal outcome. Incidence of LSCS, meconium stained liquor and low apgar score has significant correlation in patients with oligohydramnios. Incidence of low birth weight babies, NICU admissions and perinatal death was more were more are more in oligohydramnios cases. This is statistically significant (p<0.001). Conclusions: AFI <5 cm at or beyond 28 weeks of gestational age in an indicator of poor perinatal outcome. AFI measurement in antepartum or intrapartum period can help to identify women who need increased antepartum surveillance for pregnancy complications and such women should be managed in a special unit to combat the complications effectively.